Profile of secondary metabolite compounds in methanol extract of robusta coffee husk (Coffea canephora Pierre ex A. Froehner) from Jember, East Java, based on GC-MS analysis - Fawait Afnani; Prima Agusti Lukis; Faizatul Fitria; Frengky Hermawan Hadi Prasetyo; Wiwit Sri Werdi Pratiwi (AGROINTEK, 2026)
Robusta coffee husk (Coffea canephora Pierre ex A.Froehner), which has long been regarded as a low-value agricultural waste, contains bioactive compounds with promising potential for development into functional products. This study aims to identify the secondary metabolite profile of the methanol extract from robusta coffee husk originating from Jember using GC-MS analysis. Extraction was conducted by maceration with methanol, yielding a concentrated extract containing various bioactive constituents. Sixteen compounds were identified, with three major components: caffeine (55.22%), quinic acid (18.72%), and lactic acid (18.49%). These compounds exhibit diverse biological activities, including central nervous system stimulation, anticancer potential, and metabolic functions. In addition, several other compounds with antioxidant, anti-inflammatory, and antimicrobial properties were also detected. The findings indicate that robusta coffee husk from Jember has significant potential as a source of bioactive compounds for further development in functional food or pharmaceutical applications.